2021
DOI: 10.1002/nop2.1137
|View full text |Cite
|
Sign up to set email alerts
|

Perception of other healthcare professionals about the nurses' role and competencies in veno‐venous extracorporeal membrane oxygenation care: A qualitative study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Similar feelings of disrespect among nurses and the need for greater appreciation of their role in ECMO care have been reported by previous studies. 47,48 It has further been shown that such episodes of perceived injustice and credibility deficit might increase moral distress. 44 The final factor contributing to experiences of moral distress was the perceived lack of team situational awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Similar feelings of disrespect among nurses and the need for greater appreciation of their role in ECMO care have been reported by previous studies. 47,48 It has further been shown that such episodes of perceived injustice and credibility deficit might increase moral distress. 44 The final factor contributing to experiences of moral distress was the perceived lack of team situational awareness.…”
Section: Discussionmentioning
confidence: 99%
“…Regular monitoring and evaluation of patients' response to ventilation, including factors such as oxygenation levels, lung compliance, and other relevant parameters, should be conducted 41 , 42 . Moreover, interdisciplinary collaboration among healthcare teams involving respiratory therapists, critical care specialists, and other knowledgeable professionals is crucial, especially considering the shortage of experienced staff and experts in transport ventilators 41 , 43 . By implementing these measures, clinicians can increase the optimal use of ventilators, ultimately leading to improved patient survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…L'outcome degli assistiti in trattamento, in termini di sopravvivenza, è legato anche alla gestione assistenziale; in base a questi dati risulta fondamentale una formazione specifica degli infermieri, oltre a quella post-base, mediante corsi specifici come master specialistici, l'aggiornamento continuo anche mediante l'utilizzo della simulazione, al fine di migliorare le competenze del professionista e che gli permetta di specializzarsi nella gestione dei pazienti sottoposti ad ECMO. 6,15,16,20,25,26,27,35 La prevenzione e la rilevazione precoce delle complicanze, sono gli elementi chiave per un'assistenza infermieristica efficace, basata su un attento monitoraggio a 360°.…”
Section: Discussioneunclassified
“…16,18,40 Conclusioni I risultati dello studio rappresentano la letteratura esistente individuando la formazione specifica e la prevenzione delle complicanze come la chiave del successo nei pazienti sottoposti ad ECMO. 6,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Come si è visto, le procedure assistenziali giornaliere sono fondamentali nei pazienti critici poiché migliorano l'igiene, prevengono le infezioni iatrogene ed aiutano a mantenere l'integrità cutanea. L'assistenza infermieristica diventa quindi un elemento di fondamentale importanza, rispetto a questo processo, in particolar modo perché l'infermiere è la figura professionale che si relaziona per più tempo, con gli assistiti.…”
Section: Discussioneunclassified